2023
DOI: 10.3390/catal13050872
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Separable Mixed-Phase α/γ-Fe2O3 Catalyst for Photo-Fenton-like Oxidation of Rhodamine B

Abstract: Iron oxides are widely used as catalysts for photo-Fenton-like processes for dye oxidation. In this study, we report on the synthesis of an α/γ-Fe2O3 mixed-phase catalyst with magnetic properties for efficient separation. The catalyst was synthesized using glycine–nitrate precursors. The synthesized α/γ-Fe2O3 samples were characterized using scanning electron microscopy, X-ray diffraction spectroscopy (XRD), Raman shift spectroscopy, X-ray photoelectron spectroscopy (XPS), and vibrating sample magnetometer (VS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 83 publications
(90 reference statements)
0
8
0
Order By: Relevance
“…Quantitative phase analysis using the Rietveld method showed that α-Fe 2 O 3 exists as the main phase (79.6%), while γ-Fe 2 O 3 is present in a quantity of 20.4% (see Figure S2 Supplementary File) [20,23,24,[31][32][33][34][35]. The average crystallite size of the α-phase was found to be 47.4 nm, while that of the γ-phase was 45.7 nm [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative phase analysis using the Rietveld method showed that α-Fe 2 O 3 exists as the main phase (79.6%), while γ-Fe 2 O 3 is present in a quantity of 20.4% (see Figure S2 Supplementary File) [20,23,24,[31][32][33][34][35]. The average crystallite size of the α-phase was found to be 47.4 nm, while that of the γ-phase was 45.7 nm [29].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of α/γ and α-Fe 2 O 3 was carried out using the combustion method of glycine-nitrate precursors [27][28][29]. An aqueous iron (III) nitrate solution was used as the starting material, and glycine was used as the fuel.…”
Section: Methodsmentioning
confidence: 99%
“…[25] The irradiation of Fe 2 + + H 2 O 2 , also called photo-Fenton reaction, enhances the reaction rate of oxidation organic contaminants through the generation of * OH which direct attack the organics. [26] The additional use of light in the Fenton process enhances the energy of chemical processes by promoting additional photochemical reactions, such as photo-reduction of Fe 3 + to Fe 2 + and photolytic decomposition of H 2 O 2 to * OH. [27] Homogeneous Fenton has some disadvantages, such as high efficiency only in acidic conditions and the precipitation of Fe 2 + as sludge.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the growing problems associated with wastewater pollution and the need for renewable energy sources, heterogeneous photocatalysis is one of the most promising methods for wastewater treatment. However, photocatalysts have several drawbacks, such as limited light absorption ability, fast charge recombination, and being a source of secondary pollution [1–2] …”
Section: Introductionmentioning
confidence: 99%
“…However, photocatalysts have several drawbacks, such as limited light absorption ability, fast charge recombination, and being a source of secondary pollution. [1][2] In recent years, research has been conducted to overcome these drawbacks using photocatalysts with piezoelectric properties or their heterojunction systems, such as ZnO, [3] BaTiO 3 , [4] BiVO 4 /BiFeO 3 , [5] ZnO/ZnS/MoS 2 , [6] PbTiO 3 /CdS, [7] KNbO 3 , [8] NiO/ BaTiO 3 , [9] Bi 2 WO 6 /ZnSnO 3 , [10] Ag/Bi 5 O 7 I, [11] MoO x /ZnS/ZnO [12] etc. However, the issue of secondary pollution remains relevant, and these materials themselves are highly toxic.…”
Section: Introductionmentioning
confidence: 99%